Tech slump sinks Germany's Neuer Markt. - Blau, J.
Germany bade farewell at the end of September to the Frankfurt based Neuer Markt, its answer to the tech-heavy US Nasdaq stock market. in its six years of operation, Neuer Markt had treated unwary investors to more of a roller coaster ride than they bargained for, and it was plagued by scandals, despite intending to set higher standards of accountability and openness. Neuer Markt's operator, Germany's main stock exchange Deutsche Borse AG, will formally shutter the exchange at the end of 2003 and replace it with two broad segments in the main exchange, which Neuer Markt companies are being encouraged to join now. The end of the Neuer Markt caused little surprise. At its peak, companies listed on the Nemax 50 index had a market value of ?234.25 billion. Today, their value is around ?12.6 billion. Trading has all but ceased, and only one company has made an initial public offering in more than a year. The market's steep plunge has been traumatic for tech investors, who have seen billions of euros vanish.
Keywords: Deutsche Borse AG; Germany; Nemax 50 index; Neuer Markt; Main stock exchange